Анализ связи количественных характеристик женщин и полученных от них эмбрионов в программах ВРТ - Гонтарь, Ю.В.; Лахно, Я.В.; Ильин, И.Е.; Федота, А.М. (Фактори експериментальної еволюції організмів, 2016)
Aim. Analysis of relationship between response rates of women of different ages on the superovulation and embryo parameters derived from these women in programs of assisted reproductive technologies. Methods. Research of nondisjunction chromosomes in preimplantation embryos based on the results of diagnostics of 5442 from 504 ICSI + PGD programs. Stimulation of superovulation was carried out on a long luteal protocol using agonists of luteinizing hormone releasing hormone (LHRH). During the preimplantation genetic diagnosis (PGD) in the blastomeres FISH method was used. Probes for chromosomes 13, 16, 18, 21, 22, X, Y were used. Researching of relations between signs carried out by correlation analysis of Pearson and Spearman. Results. 1386 (25.5%) embryos from 5442 are defined as euploid. There is a direct correlation between the average age of women and the proportion of euploid embryos produced in one cycle of ovarian stimulation (r = 0.39), between the number of embryos per cycle in women and the number of euploid embryos per cycle (r = 0.65). There is an inverse relationship between the number of embryos per cycle of ovarian stimulation and middle-aged women (r = –0.74), between the age of patients and the number of euploid embryos per cycle of ovarian stimulation (r = –0.29), between the age of patients and the number of embryos in the ovarian cycle stimulation (r = –0.31). Conclusions. Age characteristics of the patients have a significant effect on the response to ovarian stimulation, and the number of euploid embryos stimulation cycle. Given that 75% of embryos obtained in ART programs have chromosomal aneuploidy, an effective strategy is to assign pairs of preimplantation genetic screening, where a woman’s age is critical for the prevention of chromosomal aberrations in the preimplantation period of ontogenesis. Keywords: preimplantation genetic diagnosis, assisted reproductive technologies, aneuploid embryos, response to ovarian stimulation.